Penyelesaian Pembiayaan Bermasalah pada Bank Syari’ah - Addianata, Vydika Harya; Nurnasrina, Nurnasrina; Syahfawi, Syahfawi (MUI Kota Pekanbaru, 2024)
The pattern in resolving problematic financing at Islamic banks occurs by: 1. Restructuring. Financing restructuring is one of the efforts made by the Bank in its financing disbursement business activities so that the Customer can fulfill its obligations to the Bank. Restructuring that can be done is Rescheduling, Reconditioning, Restructuring, Rescheduling 2. Settlement through guarantee Settlement through guarantee can be done by non-litigation and litigation means. 3.Collection Agent, carried out using the services of third parties such as agents / law offices or lawyers and 4. Write off: an administrative action to delete the Customer's book that has a bad collectibility from the balance sheet amounting to the Customer's total arrears without removing the Customer's billing rights. The research method used is literature research, and also the author uses qualitative research methodology. The source of data used is taken through literature related to the object of research, and then will be analyzed descriptively with deductive analysis methods with general data that has been collected and conclusions drawn.